Managing Black-throated Bobwhite for Sustainability in Belize: Preliminary Results of a Population Study - Jack Eitniear; Reynold Cal; Wilbur Martinez; Omar Fiqueroa; John Baccus (National Quail Symposium Proceedings, 2017)
The Black-throated Bobwhite (Colinus nigrogularis), a close relative of the Northern Bobwhite (C. virginianus), has a distinctive black throat and eye-stripes with both bounded by white. Black-throated Bobwhites occur in three distinct geographically isolated populations. Currently no limits or seasons are in place and a hunting license is the only requirement for harvesting this species in Belize. Little is known about Black-throated Bobwhite populations in Belize and data on the impact of hunting on this species is lacking. Because of its restricted distribution, it was recommended that Black-throated Bobwhites should be removed from the list of legally hunted species pending a better understanding of its population dynamics. In 2006 we initiated a long-term study of Black-throated Bobwhite biology at the 469 km2 Manatee Forest Reserve (henceforth MFR). Data collected at the end of the wet season indicated a population of 0.072-0.144 quail per hectare, which was appreciably lower than the density reported in the heneguen growing region of Yucatan, Mexico. Such densities predictably decreased throughout the dry season (breeding season).
Keywords: black-throated bobwhite; Belize; Colinus nigrogularis; population estimate